2012
DOI: 10.1038/cdd.2012.135
|View full text |Cite
|
Sign up to set email alerts
|

miR-125b promotes cell death by targeting spindle assembly checkpoint gene MAD1 and modulating mitotic progression

Abstract: The spindle assembly checkpoint (SAC) is a 'wait-anaphase' mechanism that has evolved in eukaryotic cells in response to the stochastic nature of chromosome-spindle attachments. In the recent past, different aspects of the SAC regulation have been described. However, the role of microRNAs in the SAC is vaguely understood. We report here that Mad1, a core SAC protein, is repressed by human miR-125b. Mad1 serves as an adaptor protein for Mad2 -which functions to inhibit anaphase entry till the chromosomal defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…However, in human cancers, mutations in SAC genes are infrequent (23). This observation led to the speculation that SAC deregulation by cancer genes and microRNA(s) may act to induce these defects (56,57). Indeed, it has been shown that the tumor suppressor protein p53 regulates the transcription of Cdc20 (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, in human cancers, mutations in SAC genes are infrequent (23). This observation led to the speculation that SAC deregulation by cancer genes and microRNA(s) may act to induce these defects (56,57). Indeed, it has been shown that the tumor suppressor protein p53 regulates the transcription of Cdc20 (30).…”
Section: Discussionmentioning
confidence: 99%
“…miR-155 is overexpressed in pancreatic cancer cells and interacts with TP53INP1 mRNA at its 3′UTR (Gironella et al, 2007), whereas miR-125b is overexpressed in type II endometrial carcinoma cells and contributes to the malignancy of type II endometrial carcinoma, possibly through down-regulation of TP53INP1 expression (Jiang et al, 2011). Regulation of TP53INP1 expression by miR-125b can be potentially important for more effective therapy, since various studies have established miR-125b as an oncogene or tumor suppressor gene in difference types of human tumors (Bousquet et al, 2010; Zhang et al, 2011; Bhattacharjya et al, 2013). …”
Section: Micro Rnas Reduce Tp53inp1 Mrna Expressionmentioning
confidence: 99%
“…In the present study we quantified nine miRNAs (miR-15a, miR-21, miR-29b, miR-34c, miR-100, miR-125b, miR-133b, miR-137 and miR-199b) in 32 samples from HNSCC, and eight of their resection margins by qRT-PCR, in order to determine whether their levels are associated with clinical pathological features. These specific miRs were chosen because they participate in the regulation of pathways considered to be “hallmarks of cancers”, such as cell death, proliferation and migration/invasion [10], [11], [12], [13], [14]. We also assessed by immunohistochemistry in six selected HNSCC samples and their matched resection margins the SET (I2PP2A) protein, involved in the promotion of cancer cell proliferation [15], and PTEN protein, a classic tumor suppressor [16].…”
Section: Introductionmentioning
confidence: 99%